(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
PCOS is a common endocrinopathy among premenopausal women, characterized by hyperandrogenism, anovulation, hirsutism. We evaluated credence of noscapine; in RU486 induced PCOS rat and compared with flutamide, a conventional drug. For 13 days, an oral dose of RU486 [20 mg/kg/day] was administered to Wistar rats exhibiting regular estrous cycle. Varying dosage of noscapine was given to PCOS rats and compared with rats administered flutamide. Cytology of estrous cycle and serum hormone levels (LH, FSH, PRL, estradiol, and testosterone) were measured. Histomorpho-metrical changes, events of apoptosis in theca and granulosa cells were observed using flow cytometry and the mode of cellular death was examined by TUNEL staining. Our findings suggested, normal folliculogenesis in PCOS rats, post noscapine administration (120 mg/kg) in 3-4 days with normal hormonal profile. Theca and granulosa cells undergo massive and marginal cellular degeneration respectively with no G2/M arrest. TUNEL staining confirms the granulosa cells in follicles are major cell type undergo apoptosis in RU486 administered rats. However, low apoptotic DNA fragmentations were found in theca cells. We conclude that the RU486 model is suitable for studies of the metabolic features of PCOS and noscapine appears to be promising therapeutic modality for amelioration of PCOS induced condition.